Effect of public health interventions on COVID-19 cases: an observational study. Issue 8 (16th February 2021) - Qiu, Weihong; He, Heng; Zhang, Peng; Yang, Wenwen; Shi, Tingming; Wang, Xing; Chen, Ailian; Xie, Li; Yang, Meng; Wang, Dongming; Li, Mingyan; Chen, Weihong
Abstract : Background: As the epidemic of COVID-19 is gradually controlled in China, a summary of epidemiological characteristics and interventions may help control its global spread. Methods: Data for COVID-19 cases in Hubei Province (capital, Wuhan) was extracted until 7 March 2020. The spatiotemporal distribution of the epidemic in four periods (before 10 January, 10–22 January, 23 January–6 February and 7 February–7 March) was evaluated, and the impacts of interventions were observed. Results: Among 67 706 COVID-19 cases, 52 111 (76.97%) were aged 30–69 years old, and 34 680 (51.22%) were women. The average daily attack rates (95% CI) were 0.5 (0.3 to 0.7), 14.2 (13.2 to 15.1), 45.7 (44.0 to 47.5) and 8.6 (7.8 to 9.3) cases per 10 6 people in four periods, and the harmonic means (95% CI) of doubling times were 4.28 (4.01 to 4.55), 3.87 (3.78 to 3.98), 5.40 (4.83 to 6.05) and 45.56 (39.70 to 52.80) days. Compared with the first period, daily attack rates rose rapidly in the second period. In the third period, 14 days after 23 January, the daily average attack rate in and outside Wuhan declined by 33.8% and 48.0%; the doubling times increased by 95.0% and 133.2%. In the four periods, 14 days after 7 February, the daily average attack rate in and outside Wuhan decreased by 79.1% and 95.2%; the doubling times increased by 79.2% and 152.0%. Conclusions: The public health interventions were associated with a reduction in COVID-19 cases in Hubei Province, especially in districts outside of Wuhan.